Minding the gap: Assessing patient expectations versus experiences in drug information services at community health centers (Puskesmas) in Indonesia urban settings - Azizah, Rezki N.; Habibie, Habibie; Arsyad, Dian S.; Bahar, Muhammad A. (Narra J, 2024)
In pharmaceutical care, patients' perceptions of drug information provided by pharmacists are vital for assessing pharmaceutical services at community health centers (in Indonesian known as Puskesmas). The aim of this study was to determine the alignment between patients' expectations and experiences of drug information services by pharmacists at Puskesmas in Indonesia. This multicenter cross-sectional study utilized a validated questionnaire among outpatient patients aged 18 years and above across all 47 Puskesmas in Makassar, Indonesia. A total of 622 respondents were interviewed between September to December 2023. Significant gaps were observed between patients' expectations and experiences regarding all the drug information aspects such as quantity (median: 4 vs 3, p<0.001), drug effects (median: 4 vs 3, p<0.001), dosage form (median: 3 vs 3, p<0.001), proper administration (median: 4 vs 4, p<0.001), side effects (median: 4 vs 2, p<0.001), storage (median: 3 vs 2, p<0.001), drug-drug interactions (median: 4 vs 2, p<0.001), drug-food interactions (median: 4 vs 2, p<0.001), handling missed dose (median: 3 vs 2, p<0.001), managing accidental overdoses (median: 4 vs 2, p<0.001), history of drug use (median: 3 vs 2, p<0.001), co-medications (median: 3 vs 2, p<0.001), and previous drug allergies (median: 3 vs 2, p<0.001). Sociodemographic factors influencing patients' need for drug information services encompass age, sex, educational attainment, comorbidities, family size, number of visits, monthly income, and occupation. The quality of drug information services at Puskesmas in Indonesia still requires optimization and customization to meet the specific needs of patients, taking into account their sociodemographic characteristics.